Method for improving physicochemical characteristics of starch and low-digestibility potato starch compound powder

Through the combination and humidity heat treatment of the ternary system of starch-protein peptide-phenol substances, the problem of improving the physical and chemical characteristics of starch in the prior art is solved, and the digestibility resistance and thermal stability of starch are improved, which is suitable for the production of low-GI foods.

CN120419677APending Publication Date: 2025-08-05DONGGUAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510669482.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-22
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently and safely improve the physical and chemical characteristics of starch in multiple dimensions, and there is a risk of chemical modification residue, high cost of enzymatic modification, and great controversy in genetic modification, which cannot meet the needs of food safety and market diversification.

Method used

By combining starch with protein peptides and phenolic substances and performing moisture heat treatment, adjusting the addition order, a ternary system of starch-protein peptides and phenolic substances is formed, and the physical and chemical characteristics of starch are improved.

Benefits of technology

It improves the digestibility of starch, reduces the swelling and viscosity of starch, enhances the thermal stability of starch, and provides the basis for the production of foods with low blood sugar production index.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120419677A_ABST
    Figure CN120419677A_ABST
Patent Text Reader

Abstract

The invention provides a method for improving physicochemical characteristics of starch and low-digestibility potato starch compound powder, and belongs to the technical field of food. According to the method for improving the physicochemical characteristics of the starch, provided by the invention, the starch, the protein peptide and the phenolic substance are compounded for use, and then the aim of improving the physicochemical characteristics of the starch is achieved through heat-moisture treatment and adjustment of the adding sequence of the protein peptide and the phenolic substance. According to the invention, heat-moisture treatment, interaction between protein peptide and starch granules, interaction between phenolic substances and starch granules and different adding sequences of protein peptide and phenolic substances in a ternary system (starch, protein peptide and phenolic substances) are proposed for the first time to jointly influence the digestion characteristics of starch. According to the technical scheme, people can be promoted to understand interaction of starch, protein and polyphenol components in food, and reference is provided for improving and perfecting a manufacturing method of low-GI (glycemic index) food.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of food technology, and particularly relates to a method for improving the physical and chemical properties of starch and a low-digestibility potato starch compound powder. Background Art

[0002] Starch, a highly abundant polysaccharide in the plant kingdom, is renewable and biodegradable, playing a crucial role in the food industry. During food production and storage, starch gelatinization and retrogradation significantly impact the texture, flavor, digestibility, and functional properties of starchy foods. Furthermore, rapidly digested starchy carbohydrates can cause a rapid rise in blood sugar levels after a meal. Long-term postprandial hyperglycemia can easily lead to abnormal insulin secretion, which in turn can induce chronic conditions such as type 2 diabetes (T2DM) and cardiovascular disease.

[0003] The physicochemical properties of starch (such as gelatinization temperature, gel strength, water holding capacity, shear resistance, acid and alkali resistance, etc.) directly determine its application effect in the fields of food, medicine, chemical industry, papermaking, etc. At present, the methods to improve the physicochemical properties of starch mainly include physical modification, chemical modification, enzymatic modification and genetic modification, but there are certain technical bottlenecks: physical modification technology has limited effect on the molecular structure of starch, and it is difficult to achieve directional regulation of properties (such as only slightly increasing the gelatinization temperature or reducing transparency), and industrial production has high energy consumption, large equipment investment, poor processing uniformity, and insufficient batch stability. Chemical modification technology requires the use of chemical reagents (such as acetic anhydride, epichlorohydrin), which has a residual risk and is difficult to pass food safety certification (such as the EU clean label requirements). Moreover, the modification process may destroy the natural structure of starch, resulting in an imbalance of functional properties (such as a significant decrease in the gelatinization ability of cross-linked starch). In addition, chemical waste liquid treatment increases production costs, which is not in line with the development trend of green chemistry. Due to the specificity of enzyme action, enzymatic modification technology cannot achieve multi-dimensional property improvements (such as improving acid resistance and gel strength at the same time) with a single enzyme treatment; the enzymatic reaction conditions are harsh (temperature and pH value must be strictly controlled), and the cost of enzyme recycling in industrial production is high; the modification cycle is long, and the efficiency is lower than that of chemical or physical methods. Genetic modification technology has high technical barriers, long R&D cycles, and faces controversy over the safety of genetically modified crops; it is only applicable to specific crops (such as corn and potatoes), and its scope of application is limited; it is difficult to quickly respond to the market's diverse demands for starch properties. Therefore, this field currently lacks a technical solution that is efficient, safe, scalable, and can improve the physical and chemical properties of starch in multiple dimensions.

[0004] Protein peptides are important active protein substances with advantages such as low viscosity, good solubility, high activity, easy digestion and absorption, and low antigenicity. They play an important role in nutritional regulation and immune regulation. However, there is currently a lack of research on the interaction between protein peptides and starch and their impact on starch properties. In addition, although there are related studies on starch and phenolic substances and starch and protein peptides in this field, the overall research on the three is still limited, and new exploration directions are urgently needed to promote the development of multi-phase, multi-component food systems. Summary of the Invention

[0005] In view of this, one of the objects of the present invention is to provide a method for improving the physicochemical properties of starch.

[0006] A second object of the present invention is to provide a method for improving the digestibility of starch.

[0007] The third object of the present invention is to provide a low-digestibility potato starch compound powder and its preparation method and application.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] The present invention provides a method for improving the physicochemical properties of starch, the method comprising a or b:

[0010] a. Mix starch and protein peptide, react at 100℃ for 1h, then mix with phenolic substances and react at 100℃ for 17h;

[0011] b. Mix starch with phenolic substances, react at 100°C for 1 hour, then mix with protein peptides, and react at 100°C for 17 hours;

[0012] The starch includes potato starch; the protein peptide includes rice peptide or pea peptide; and the phenolic substance includes quercetin or catechin.

[0013] Preferably, the physicochemical properties of starch include swelling capacity, gelatinization temperature, viscosity, crystal structure, density and order.

[0014] Preferably, if the swelling degree or viscosity of starch is to be reduced, then a is selected; if the gelatinization temperature of starch is to be reduced or the density and order of starch are to be maintained, then b is selected.

[0015] Preferably, the weight of the protein peptide is 10% of the dry weight of starch; the weight of the phenolic substance is 10% of the dry weight of starch.

[0016] The present invention also provides a method for improving the digestibility of starch, comprising the following steps: mixing starch with water until the moisture content of the starch reaches 35%, mixing with phenolic substances after equilibration at room temperature, reacting at 100°C for 1 hour, adding protein peptides, and reacting at 100°C for 17 hours; the starch comprises potato starch; the protein peptides comprise rice peptides or pea peptides; and the phenolic substances comprise quercetin or catechins.

[0017] Preferably, the room temperature equilibration time is 24 hours.

[0018] Preferably, the weight of the protein peptide is 10% of the dry weight of starch; the weight of the phenolic substance is 10% of the dry weight of starch.

[0019] The present invention also provides a low-digestibility potato starch compound powder, which is obtained by mixing potato starch, protein peptide and phenolic substances in the order of potato starch first, phenolic substances and protein peptide, and subjecting the mixture to wet heat treatment; the weight of the protein peptide is 10% of the weight of the starch dry basis; the weight of the phenolic substances is 10% of the weight of the starch dry basis; the protein peptide comprises rice peptide or pea peptide; and the phenolic substances comprises quercetin or catechin.

[0020] The present invention also provides a method for preparing the low-digestibility potato starch compound powder, comprising the following steps: mixing potato starch with water until the moisture content of the potato starch reaches 35%, mixing with phenolic substances after equilibration at room temperature, reacting at 100° C. for 1 hour, adding protein peptides, and reacting at 100° C. for 17 hours; the protein peptides include rice peptides or pea peptides; and the phenolic substances include quercetin or catechins.

[0021] The present invention also provides the use of the method, the low-digestibility potato starch compound powder or the preparation method in preparing low-GI food.

[0022] Beneficial effects of the present invention:

[0023] The present invention proposes for the first time that starch, protein peptide and phenolic substances are compounded and then the physicochemical properties of starch can be improved by heat-moisture treatment and adjusting the order of adding the protein peptide and phenolic substances.

[0024] This study, published in the journal Nature Communications, proposes for the first time that heat-moisture treatment, the interaction between protein peptides and starch granules, the interaction between phenolics and starch granules, and the order of addition of protein peptides and phenolics in a ternary system (starch, protein peptides, and phenolics) all contribute to the digestibility of potato starch. This technical solution can enhance understanding of the interactions between starch, protein, and polyphenols in foods and provide a reference for improving and refining methods for producing low-GI (glycemic index) foods. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1The expansion test results of different groups of Example 1 and Comparative Example 1 are shown;

[0026] Figure 2 The viscosity curves of different groups of Example 1 and Comparative Example 1 are shown. Some curves of different colors overlap because the viscosity is too low.

[0027] Figure 3 The X-ray diffraction patterns of different groups of Example 1 and Comparative Example 1 are shown;

[0028] Figure 4 The viscosity curves of different groups of Example 2 and Comparative Example 2 are shown. Some curves of different colors overlap because the viscosity is too low.

[0029] Figure 5 The X-ray diffraction patterns of different groups of Example 2 and Comparative Example 2 are shown. DETAILED DESCRIPTION

[0030] The present invention provides a method for improving the physicochemical properties of starch, the method comprising a or b:

[0031] b. Mix starch and protein peptide, react at 100℃ for 1 hour, then mix with phenolic substances, and react at 100℃ for 17 hours;

[0032] b. Mix starch with phenolic substances, react at 100°C for 1 hour, then mix with protein peptides, and react at 100°C for 17 hours;

[0033] The starch includes potato starch; the protein peptide includes rice peptide or pea peptide; and the phenolic substance includes quercetin or catechin.

[0034] In the present invention, the physicochemical properties of the starch preferably include swelling degree, gelatinization temperature, viscosity, crystal structure, as well as density and order. In the present invention, if the swelling degree or viscosity of starch is to be reduced, a is selected; if the gelatinization temperature of starch is to be reduced or the density and order of starch is to be maintained, b is selected. In the present invention, the weight of the protein peptide is preferably 10% of the dry weight of starch; the weight of the phenolic substance is preferably 10% of the dry weight of starch. The present invention has no special restrictions on the specific sources of the above-mentioned raw materials, and conventional commercial products in the field can be used. In the present invention, when the protein peptide is rice peptide, the phenolic substance is preferably quercetin; when the protein peptide is pea peptide, the phenolic substance is preferably catechin.

[0035] At present, in the field of food industry, there are few studies on the mechanism and effectiveness of the interaction of starch-protein peptide-phenolic substance ternary system. Starch, protein peptide and phenolic substance are all important components in food. Their ternary complex has multiple functional properties, especially phenolic substance-protein peptide has a significant effect on the digestibility of starch. The changes in swelling degree, viscosity, thermodynamic properties, bioavailability of polyphenols, etc. in the ternary system are studied to improve the stability of polyphenol compounds in food production and processing or under digestive conditions. This will greatly benefit the application and development of starch-protein peptide-phenolic substance ternary complex. The present invention studies the morphological characteristics, crystal structure, thermodynamic properties and rheological properties of the composite system, understands the law of its interaction, and establishes the intrinsic correlation with starch digestibility. At the same time, the differences in physicochemical properties and functional properties between the starch-protein peptide-phenolic substance ternary complex system and ordinary starch are explored, providing a theoretical basis for the application of the starch-protein peptide-phenolic substance ternary complex system in the food industry.

[0036] The present invention constructs a starch-protein peptide-phenolic ternary complex system under both cooked and uncooked conditions. The water swelling capacity of the complex is measured; the viscosity of the complex is investigated using a Brabender viscometer; the thermodynamic properties of the complex are analyzed using a differential scanning calorimeter; the unit cell structure of the complex is analyzed using a small-angle X-ray scattering instrument; and the crystallization properties of the complex are investigated using an X-ray diffractometer. The in vitro digestibility of the ternary complex is analyzed using an in vitro digestion method; and the interactions of the starch-protein peptide-phenolic ternary system and the differences in in vitro digestibility of the systems are investigated.

[0037] The present invention also provides a method for improving the digestibility of starch, comprising the following steps: mixing starch with water until the moisture content of the starch reaches 35%, mixing with phenolic substances after equilibration at room temperature, reacting at 100°C for 1 hour, adding protein peptides, and reacting at 100°C for 17 hours; the starch comprises potato starch; the protein peptides comprise rice peptides or pea peptides; and the phenolic substances comprise quercetin or catechins.

[0038] In the present invention, the room temperature equilibration time is preferably 24 hours, and the room temperature is preferably 20° C. to 25° C. In the present invention, the weight of the protein peptide is preferably 10% of the dry weight of starch; the weight of the phenolic substance is preferably 10% of the dry weight of starch.

[0039] The present invention also provides a low-digestibility potato starch compound powder, which is obtained by mixing potato starch, protein peptide, and phenolic substances in the order of potato starch first, phenolic substances, and protein peptide, and subjecting the mixture to a wet heat treatment; the weight of the protein peptide is 10% of the weight of the starch on a dry basis; the weight of the phenolic substances is 10% of the weight of the starch on a dry basis; the protein peptide comprises rice peptide or pea peptide; and the phenolic substances comprises quercetin or catechin. In the present invention, the wet heat treatment method preferably comprises mixing the potato starch and phenolic substances, reacting at 100° C. for 1 hour, then adding the protein peptide, and reacting at 100° C. for 17 hours.

[0040] The present invention also provides a method for preparing the low-digestibility potato starch compound powder, comprising the following steps: mixing potato starch with water until the moisture content of the potato starch reaches 35%, mixing with phenolic substances after equilibration at room temperature, reacting at 100° C. for 1 hour, adding protein peptides, and reacting at 100° C. for 17 hours; the protein peptides include rice peptides or pea peptides; and the phenolic substances include quercetin or catechins.

[0041] The present invention also provides the use of the method, the low-digestibility potato starch compound powder or the preparation method in preparing low-GI food.

[0042] In the present invention, the effects of protein peptides on the digestibility of starch are mainly in the following aspects: 1. Delaying the digestion rate of starch: The digestion rate of starch in the small intestine can be delayed by protein peptides, so that starch is gradually released into the small intestine, slowing down the rate of increase in blood sugar. 2. Promoting insulin secretion: The intake of protein peptides can promote the secretion of insulin, thereby promoting the conversion of starch into glucose. 3. Affecting the digestive enzymes of starch. The effects of phenolic substances on starch are mainly in the following aspects: 1. Inhibiting amylase activity: It can reduce the activity of amylase, thereby slowing down the digestion rate of starch. 2. Forming a complex with starch, thereby slowing down the digestion rate of starch. 3. Promoting the production of short-chain fatty acids, which can promote gastrointestinal health and regulate blood sugar and insulin levels.

[0043] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0044] In the following examples, unless otherwise specified, all methods are conventional.

[0045] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0046] The rice peptide (food grade) and pea peptide in the following examples were purchased from Xi'an Green Spring Biotechnology Co., Ltd.; potato starch (edible grade) was purchased from Hangzhou Prostar Starch Co., Ltd.; quercetin (purity ≥98%) was purchased from Shanghai Yuanye Biotechnology Co., Ltd.; catechin was purchased from Shanghai Yuanye Biotechnology Co., Ltd.; and porcine pancreatic α-amylase (≥1000 units / mg) was purchased from Sigma-Aldrich, USA.

[0047] Example 1

[0048] A method for improving the physicochemical properties of potato starch, the method being a or b:

[0049] a. 20 g of potato starch on a dry basis was mixed with deionized water to a moisture content of 35% and equilibrated at room temperature for 24 h. Rice peptide (10% by mass of the potato starch on a dry basis) was then added and stirred. The mixture was placed in a reactor and placed in a 100°C convection oven for 1 h. Quercetin (10% by mass of the potato starch on a dry basis) was added, stirred and mixed, and the mixture was returned to a reactor, which was then placed in a 100°C convection oven for 17 h. The sample was removed and cooled to room temperature, dried overnight at 37°C, and pulverized to pass through an 80-mesh sieve.

[0050] b. 20 g of potato starch dry basis was mixed with deionized water to a moisture content of 35% and equilibrated at room temperature for 24 h. Quercetin (10% by mass of the potato starch dry basis) was then added and stirred. The mixture was placed in a reactor and placed in a 100°C convection oven for reaction for 1 h. Rice peptide (10% by mass of the potato starch dry basis) was added, stirred and mixed, and the mixture was placed in a reactor again, placed in a 100°C convection oven for reaction for 17 h. The sample was taken out and cooled to room temperature, dried overnight at 37°C, and pulverized to pass through an 80-mesh sieve.

[0051] Example 2

[0052] A method for improving the physicochemical properties of potato starch, the method being a or b:

[0053] a. Mix 20g of potato starch dry basis with deionized water to make the moisture content of the potato starch sample reach 35%, and equilibrate at room temperature for 24 hours. Then, add pea peptide at a mass fraction of 10% of the potato starch dry basis and stir to mix. The mixture is placed in a reactor and placed in a vacuum drying oven at 100°C for wet heat treatment for 1 hour. Add catechin at a mass fraction of 10% of the potato starch dry basis, stir and mix, then put back into the reactor, place in a vacuum drying oven, and wet heat treatment at 100°C for 17 hours. Take out, cool to room temperature, place in a forced air oven at 37°C for 24 hours, and then crush and pass through a 100-mesh sieve.

[0054] b. Mix 20 g of potato starch dry basis with deionized water to make the moisture content of the potato starch sample reach 35%, and equilibrate at room temperature for 24 hours. Then, add catechins at a mass fraction of 10% of the potato starch dry basis and stir to mix. The mixture is placed in a reactor and placed in a vacuum drying oven at 100°C for wet heat treatment for 1 hour. Add pea peptides at a mass fraction of 10% of the potato starch dry basis, stir and mix, then put back into the reactor, place in a vacuum drying oven, and wet heat treatment at 100°C for 17 hours. Take out, cool to room temperature, place in a forced air oven at 37°C for 24 hours, and then crush and pass through a 100-mesh sieve.

[0055] Example 3

[0056] A method for reducing the swelling degree or viscosity of potato starch, specifically a in Example 1.

[0057] Example 4

[0058] A method for reducing the swelling degree or viscosity of potato starch, specifically a in Example 2.

[0059] Example 5

[0060] A method for lowering the gelatinization temperature of potato starch, or maintaining the density and orderliness of potato starch, specifically the method b in Example 1.

[0061] Example 6

[0062] A method for lowering the gelatinization temperature of potato starch, or maintaining the density and orderliness of potato starch, specifically the method b in Example 2.

[0063] Example 7

[0064] A method for improving the physicochemical properties of potato starch, the method being a or b:

[0065] a. 20 g of potato starch on a dry basis was mixed with deionized water to a moisture content of 35% and equilibrated at room temperature for 24 h. Rice peptide (10% by mass of the potato starch on a dry basis) was then added and stirred. The mixture was placed in a reactor and placed in a 100° C. convection oven for 1 h. Catechin (10% by mass of the potato starch on a dry basis) was added, stirred and mixed, and the mixture was returned to a reactor, which was then placed in a 100° C. convection oven for 17 h. The sample was removed, cooled to room temperature, dried overnight at 37° C., and pulverized through an 80-mesh sieve.

[0066] b. 20 g of potato starch on a dry basis was mixed with deionized water to a moisture content of 35% and equilibrated at room temperature for 24 h. The sample was then added with catechins (10% by mass of the potato starch on a dry basis) and stirred. The mixture was placed in a reactor and placed in a 100° C. convection oven for 1 h. Rice peptides (10% by mass of the potato starch on a dry basis) were added, stirred and mixed, and the mixture was returned to a reactor, which was then placed in a 100° C. convection oven for 17 h. The sample was removed and cooled to room temperature, dried overnight at 37° C., and pulverized to pass through an 80-mesh sieve.

[0067] Example 8

[0068] A method for improving the digestibility of starch, specifically the method b in Example 1.

[0069] Example 9

[0070] A method for improving the digestibility of starch, specifically b in Example 2.

[0071] Example 10

[0072] A low-digestibility potato starch compound powder is obtained by mixing potato starch, 10% rice peptide based on the dry weight of potato starch and 10% quercetin based on the dry weight of potato starch in the order of potato starch, quercetin and rice peptide, and then subjecting the mixture to a wet heat treatment.

[0073] The preparation method is the same as that in Example 1.

[0074] Example 11

[0075] A low-digestibility potato starch compound powder is obtained by mixing potato starch, pea peptide containing 10% of the dry weight of potato starch and catechin containing 10% of the dry weight of potato starch in the order of potato starch, catechin and pea peptide, and then subjecting the mixture to a wet heat treatment.

[0076] The preparation method is the same as that in Example 2.

[0077] Comparative Example 1

[0078] The difference from a in Example 1 is that it does not contain quercetin. All the other are the same as a in Example 1, specifically: 20g potato starch dry basis is mixed with deionized water to make the moisture content of the potato starch sample reach 35%, and equilibrate at room temperature for 24h, then add 10% mass fraction of rice peptide of potato starch dry basis and stir and mix, the mixture is placed in a reactor, placed in a 100℃ forced air drying oven and reacted for 1h; then continue to react in a 100℃ forced air drying oven for 17h; take out, cool to room temperature, dry overnight at 37℃, pulverize and pass through an 80-mesh sieve. The sample obtained is recorded as PS-RPT (RPT represents rice peptide, PS represents potato starch).

[0079] The difference from Example 1 (b) is that it does not contain rice peptide. The rest is the same as Example 1 (b), specifically: 20g of potato starch dry basis is mixed with deionized water to make the moisture content of the potato starch sample reach 35%, and equilibrated at room temperature for 24h, then 10% mass fraction of quercetin on a potato starch dry basis is added and stirred, the mixture is placed in a reactor, placed in a 100°C forced air oven to react for 1h; the reaction is continued in a 100°C forced air oven for 17h; taken out, cooled to room temperature, dried overnight at 37°C, pulverized and passed through an 80-mesh sieve. The obtained sample is recorded as PS-Q (Q represents quercetin).

[0080] The sample obtained in Example 1a was recorded as PS-RPT-Q, and the sample obtained in Example 1b was recorded as PS-Q-RPT.

[0081] The potato starch without rice peptide and quercetin and only subjected to heat treatment was used as a control group. Specifically, 20g of potato starch was mixed with deionized water to make the moisture content of the potato starch sample reach 35%, and then equilibrated at room temperature for 24 hours. Then, it was placed in a reactor and placed in a 100℃ forced air oven to react for 1 hour; the reaction was continued in a 100℃ forced air oven for 17 hours; it was taken out and cooled to room temperature, dried at 37℃ overnight, crushed and passed through an 80-mesh sieve. The obtained sample was recorded as PS control .

[0082] Potato starch without rice peptide and quercetin addition and without heat treatment was labeled as PS native .

[0083] The above PS control , PS-RPT, PS-Q, PS-RPT-Q, PS-Q-RPT and PS native Perform the following tests:

[0084] (1) Determination of expansion

[0085] Weigh 0.2g of dry sample into a centrifuge tube and place in a rotor (a blank control group is also set up). Add deionized water and mix thoroughly to prepare a 10% starch emulsion. Place the prepared starch emulsion in a water bath at 60°C, 70°C, 80°C, and 90°C for 30 minutes of water bath stirring, then centrifuge at 3000 rpm for 15 minutes. After centrifugation, remove the centrifuge tube and pour out the supernatant. Based on the remaining solid mass (referring to the mass of expanded starch), the degree of expansion of each sample after the high-temperature water bath is calculated according to the following formula.

[0086] Expansion degree (%) = (mass of expanded starch / mass of starch dry basis) × 100

[0087] The results are as follows Figure 1 As shown in Table 1. Figure 1 It can be seen that the swelling degree of both pure starch and starch composite after heat and moisture treatment increases with the increase of temperature. native ) compared to starch treated with moist heat (PS control ) is significantly reduced, which is mainly attributed to the fact that under the combined action of water and heat during the wet heat treatment, the internal structure of starch molecules changes, and they reassemble to form denser aggregates, and the amorphous area of starch is reduced, resulting in a decrease in water absorption and expansion capacity.

[0088] From the swelling data in Table 1, in the binary system (potato starch and rice peptide, or potato starch and quercetin), the swelling rate of the two components is the same as that of the two components (potato starch and rice peptide, or potato starch and quercetin). control In comparison, whether adding rice peptide or quercetin, the starch swelling degree decreased slightly under the conditions of 60℃, 80℃ and 90℃. The reasons for this are that for PS-RPT, (1) there are hydrophobic, electrostatic, and hydrogen bond interactions between rice peptide molecules and starch molecules, which are enhanced during the wet heat treatment process, and the internal structure of the molecules is rearranged to form a more complex and compact reorganization structure; (2) at the same time, rice peptide will be adsorbed on the surface of starch granules to hinder their water absorption and swelling. For PS-Q, wet heat treatment enhances the interaction between the two and enhances the ordered structure of starch internal aggregates. Compared with rice peptide, quercetin has a more significant effect on starch swelling degree. This may be because quercetin has a smaller molecular weight and the interaction between it and starch is stronger during the wet heat treatment process.

[0089] Compared with binary systems, ternary complexes generally exhibit lower swelling capacity. Within the ternary complexes, the swelling of the starch complexes varied depending on the order in which rice peptides and quercetin were added. Under the same heat-moisture treatment conditions, the swelling of PS-RPT-Q was lower than that of PS-Q-RPT, indicating that the preferential mixing of starch and rice peptides can effectively reduce the swelling of starch granules in water. This may be due to the different complexing abilities of rice peptides and quercetin on starch granules, resulting in different structural compactness of the formed complexes. This provides valuable guidance on the impact of the order in which different components are added during food processing on the functional properties of foods.

[0090] Table 1 Expansion data of samples in different groups

[0091] Sample 60℃ 70℃ 80℃ 90℃ <![CDATA[PS native ]]> <![CDATA[nd a ]]> <![CDATA[nd a ]]> <![CDATA[nd a ]]> <![CDATA[nd a ]]> <![CDATA[PS control ]]> <![CDATA[5.15±0.36 b ]]> <![CDATA[5.44±0.28 bc ]]> <![CDATA[7.68±0.49 b ]]> <![CDATA[9.08±0.81 b ]]> PS-Q <![CDATA[4.64±0.44 b ]]> <![CDATA[5.56±0.35 b ]]> <![CDATA[6.34±0.43 b ]]> <![CDATA[7.32±0.55 bc ]]> PS-RPT <![CDATA[5.10±0.45 b ]]> <![CDATA[5.73±0.29 b ]]> <![CDATA[7.45±0.45 b ]]> <![CDATA[7.30±1.60 bc ]]> PS-Q-RPT <![CDATA[4.76±0.07 b ]]> <![CDATA[6.51±0.16 c ]]> <![CDATA[7.05±0.47 b ]]> <![CDATA[7.03±0.69 c ]]> PS-RPT-Q <![CDATA[4.67±0.32 b ]]> <![CDATA[4.85±0.48 c ]]> <![CDATA[6.02±0.12 c ]]> <![CDATA[6.84±1.36 c ]]>

[0092] Note: nd means complete expansion, and the expansion degree was not measured. Different superscript letters in the same column of data indicate significant differences (P < 0.05); identical superscript letters indicate no significant differences (P > 0.05).

[0093] (2) Viscosity measurement

[0094] Add deionized water to prepare 20 mL of a 6% starch emulsion. Mix thoroughly, transfer the mixture to a measuring cup, and measure viscosity using a Brabender viscometer. Set the starting temperature to 30°C, raise the temperature to 95°C at a rate of 6°C / min, hold for 5 minutes, then cool at a rate of 7.5°C / min to 50°C, hold for 5 minutes, and then terminate the measurement. Record the viscosity data and temperature curve.

[0095] The results are as follows Figure 2 As shown in Table 2. Figure 2 As can be clearly seen from Table 2, native In comparison, PS control The pasting temperature (PT) increased significantly, while the peak viscosity (PV), hot pasting viscosity (HV), and cold pasting viscosity (CV) decreased significantly. This is primarily due to the intense movement and collisions of starch molecules under the wet heat treatment, which rearranges the internal molecular chains, forming a new, more compact and ordered structure. This effectively reduces the starch's ability to bind to water, thereby inhibiting the swelling of starch granules. Simultaneously, cross-linking between granules enhances hydrogen bonding, leading to the extraction of amylose and increasing the starch's heat resistance, thereby reducing starch viscosity.

[0096] After heat treatment, the PT, PV, HV and CV of the binary complex with rice peptide and quercetin were lower than those of PS. control This is mainly attributed to the fact that the addition of rice peptides and / or quercetin reduces the ability of starch to bind to water, thereby enhancing the thermal stability of the binary complex. In PS-Q, quercetin molecules have more hydroxyl groups, which compete with starch molecules for water molecules during the gelatinization process, thereby inhibiting the dissolution and swelling of starch to a certain extent and reducing starch viscosity. In PS-RPT, the denatured protein after heating will enhance the integrity of the starch.

[0097] In the ternary complex, the order of adding rice peptides and quercetin varied. During gelatinization, the PV, HV, and CV of PS-RPT-Q were lower than those of PS-Q-RPT, while the PT was higher. Experiments have shown that the preferential mixing of starch and rice peptides can effectively reduce starch viscosity.

[0098] Table 2 Viscosity characteristics data of different groups

[0099] sample PT / ℃ PV / BU HV / BU CV / BU BD / BU SB / BU <![CDATA[PS native ]]> 67.9 4380 1425 2527 3233 637 <![CDATA[PS control ]]> 88.6 60 155 95 0 95 PS-Q 86.1 25 50 25 0 26 PS-RPT 86.9 11 17 7 1 8 PS-Q-RPT 84.1 11 20 9 1 10 PS-RPT-Q 86.8 9 12 4 1 5

[0100] (3) Differential calorimetry analysis

[0101] Weigh 0.003g of dry sample and add deionized water to prepare a starch emulsion with a mass fraction of 30%. The water content was balanced in a sealed environment for 2 hours. A differential calorimeter was used to scan the sample at 30-120℃ in a sealed aluminum pan at a rate of 10℃ / min (a blank aluminum pan was used as a control). The results were analyzed to determine the thermodynamic characteristic parameters of the sample: the initial gelatinization temperature (T o ), peak gelatinization temperature (T p ), final gelatinization temperature (T c ) and enthalpy (ΔH).

[0102] The results are shown in Table 3. control After wet heat treatment, T o 、T p and T c Compared with PS native After heat treatment, the starch composites with rice peptides and / or quercetin showed a significant increase in T o 、T p and T c Both lower than PS control Compared with the binary composite system, the order of adding rice peptide and quercetin in the ternary composite system is different, and the thermodynamic characteristics are also different. o 、T p and T c This indicates that the preferential compounding of starch and soybean peptides can effectively increase the gelatinization temperature of starch. It also proves that the tightness of the complex formed by protein and starch is better than that of starch-polyphenol complex, which better hinders the transfer of heat, improves the thermal stability of starch, and requires more heat for gelatinization.

[0103] Table 3 Thermodynamic properties data of different groups

[0104] Sample <![CDATA[T o (℃)]]> <![CDATA[T p (℃)]]> <![CDATA[T c (℃)]]> ΔH(J / g) <![CDATA[PS native ]]> <![CDATA[60.89±0.26 c ]]> <![CDATA[65.86±0.02 e ]]> <![CDATA[72.85±0.64 d ]]> <![CDATA[20.97±2.38 b ]]> <![CDATA[PS control ]]> <![CDATA[78.57±1.00 a ]]> <![CDATA[85.56±0.09 a ]]> <![CDATA[96.58±2.94 a ]]> <![CDATA[11.49±5.15 a ]]> PS-Q <![CDATA[78.47±2.94 a ]]> <![CDATA[83.83±0.24 bc ]]> <![CDATA[92.15±1.41 b ]]> <![CDATA[11.46±1.36 a ]]> PS-RPT <![CDATA[78.22±0.41 a ]]> <![CDATA[84.33±0.59 b ]]> <![CDATA[91.90±0.97 b ]]> <![CDATA[10.79±1.12 a ]]> PS-Q-RPT <![CDATA[70.23±0.47 b ]]> <![CDATA[78.12±0.34 d ]]> <![CDATA[86.06±0.26 c ]]> <![CDATA[10.72±0.20 a ]]> PS-RPT-Q <![CDATA[76.69±0.45 a ]]> <![CDATA[79.95±0.34 c ]]> <![CDATA[91.03±0.82 b ]]> <![CDATA[7.99±1.36 a ]]>

[0105] Note: If the superscript letters of the data in the same column are different, it means there is a significant difference (P < 0.05); if the superscript letters are the same, it means there is no significant difference (P > 0.05).

[0106] (4) X-ray diffraction

[0107] The sample was placed at room temperature (25°C) to equilibrate moisture for 24 hours. X-ray diffraction measurements were performed using the XRD diffractometer sample stage. Parameters were set: scanning angle range 4° to 35°, temperature 25°C. After completion, relative crystallinity was calculated using MDJjade 6.5 software.

[0108] The results are as follows Figure 3 As shown in the figure, the crystalline structure of starch can be divided into four categories: A-type, B-type, C-type and V-type according to the differences in X-ray diffraction patterns. Type A mainly comes from cereal starch; Type B mainly comes from tuber starch; Type C is a mixed crystal form of Type A and Type B; Type V is formed by the complexation of amylose with non-polar or weakly polar substances. Figure 3 As can be seen, PS native There are diffraction peaks at 5.6°, 15°, 17°, 22°, and 24°; PS control Diffraction peaks were observed at 15°, 17°, 18°, and 23° for PS-RPT; at 15°, 17°, and 23° for PS-Q; at 11°, 13°, 15°, 17°, 23°, and 26° for PS-RPT-Q; and at 11°, 13°, 17°, 23°, and 26° for PS-Q-RPT. This indicates that potato starch has a typical B-type crystal structure, which transforms into a typical A-type crystal structure after heat treatment. PS-RPT also has an A-type crystal structure, while PS-Q, PS-RPT-Q, and PS-Q-RPT all have a C+V-type crystal structure. Experiments have shown that the addition of quercetin under heat treatment significantly alters the crystalline structure of starch granules.

[0109] (5) In vitro digestibility assay

[0110] 5.1 Preparation of buffer solution

[0111] Accurately weigh 13.6 g of solid CH₃COONa·2H₂O and dissolve it in 250 mL of saturated benzoic acid solution. Add deionized water to 1 L. Adjust the pH to 5.2 using 0.1 mol / L acetic acid. Finally, add 4 mL of 1 mol / L CaCl₂ solution.

[0112] 5.2 Preparation of enzymatic solution

[0113] Accurately weigh 6.3mL of amyloglucosidase and add 7.2mL of deionized water to mix evenly. Accurately weigh 4 portions of 6.0000g of porcine pancreatic α-amylase and add them to 4 100mL centrifuge tubes. Add 40mL of deionized water to each tube and mix them evenly. Stir magnetically for 10 minutes, then place them in a refrigerated centrifuge and centrifuge them at 4°C and 3500rpm for 10 minutes. After centrifugation, draw 27mL of supernatant (a total of 108mL) from each of the 4 centrifuge tubes into a clean small beaker, add 12mL of diluted amyloglucosidase solution, and add 8mL of deionized water to mix them evenly.

[0114] 5.3 Sample preparation

[0115] Accurately weigh 0.6000g of dry sample (simultaneously serving as a blank control) and place it into five 50mL centrifuge tubes. Place a magnetic rotor in each tube. Add 20mL of buffer solution to each tube and vortex mix thoroughly. Place the tube in a boiling water bath using a magnetic stirrer for 30 minutes (a boiling water bath is not required for determining the digestibility of uncooked starch). Maintain magnetic stirring (800 rpm) throughout the boiling water bath to maintain mixing. Cool the tube in a 37°C water bath.

[0116] 5.4 In vitro digestion experiment

[0117] The centrifuge tubes containing the samples prepared in the previous step were placed in a 37°C constant temperature shaking water bath (160rpm / min). After a period of time, 5mL of enzymatic solution was added to each tube (1min interval between each tube), and after sufficient shaking and mixing, they were returned to the water bath for insulation. Each tube was taken out after 20min of insulation, and the liquid in the 0.25mL tube was drawn and placed in a 15mL centrifuge tube containing 10mL of 66% ethanol for enzyme inactivation. Subsequently, the vortex was mixed and the 50mL centrifuge tube was immediately returned to the water bath constant temperature shaker. The sample after enzyme inactivation was recorded as G20. After that, sample G20 was placed in a centrifuge and centrifuged at 3500rpm for 10min. After each tube was incubated for 120min, 0.25mL of enzymatic solution was taken out again and the treatment method was the same as G20, recorded as G120.

[0118] 5.5 Determination of glucose content

[0119] Prepare GOPOD solution according to the Megazyme D-GLUCOSEASSAY PROCEDURE. Pipette 3 mL of GOPOD solution into a 5 mL brown centrifuge tube and add 0.1 mL of each of the blank control, treated samples (G20 and G120), and glucose standard solution. Vortex mix thoroughly and place in a 50°C water bath for 20 minutes (protect from light). After the reaction, cool the tube in ice water for a few minutes and measure the absorbance at 510 nm.

[0120] 5.6 Calculation and Results

[0121] After completing the above steps, the glucose content of each sample was calculated according to the following formula.

[0122] Glucose content (%) = [(A t ×V t ×C×D) / (A s ×W t )]

[0123] Where: A t —Absorbance of the test solution; V t—Total volume of test solution; C—Standard concentration (mg glucose / mL); D—Dilution factor; A s —absorbance value of standard glucose; W t —The weight of the sample.

[0124] The contents of rapidly digestible starch, slowly digestible starch and resistant starch in each sample were calculated according to the following formulas.

[0125] RDS=(G20-FG)×0.9

[0126] SDS=(G120-G20)×0.9

[0127] RS=TS-(RDS+SDS)=TS-(G120×0.9)

[0128] Where: RDS - rapidly digestible starch; FG - initial glucose content (based on 0); SDS - slowly digestible starch; RS - resistant starch; TS - total starch.

[0129] The in vitro digestibility results of different groups under uncooked and cooked conditions are shown in Tables 4 and 5, respectively. Under uncooked conditions, heat treatment can significantly increase the RDS content of starch while reducing the RS content. Experiments have shown that heat treatment can improve the digestibility of ungelatinized starch. Under heat treatment conditions, the RDS content of binary and ternary complexes is lower than that of PS. control . In PS-RPT, there is an interaction between the side chain groups of rice peptides and the double helix structure inside starch, and the molecules are rearranged to form a tightly structured complex. Peptides attached to the surface of starch granules will hinder the attachment of starch digestive enzymes, and some proteins in a free state will also compete with starch granules for binding to digestive enzymes. These situations will increase the difficulty of starch digestion and increase the RS content. In PS-Q, in addition to forming a tightly ordered complex through interaction, quercetin polyphenol molecules can interact with digestive enzymes, reduce enzyme activity, prevent starch hydrolysis, and inhibit starch digestion. Compared with the binary complex system, the RDS content of the ternary complex systems PS-RPT-Q and PS-Q-RPT are lower than those of PS-RPT and PS-Q, while the RS content is significantly increased, which proves that the ternary complex system is better than the binary complex system in reducing the digestibility of starch.

[0130] Under cooking conditions, the RDS content of all samples increased significantly compared to those without cooking, while the SDS and RS contents decreased significantly. This is because starch gelatinization occurred during cooking, and the stable and orderly internal structure was destroyed, which is conducive to digestion. The RDS content of the composites after cooking was lower than that of PS. control , the ternary system can better inhibit starch digestion than the binary system.

[0131] Regardless of whether the treatment was steamed or uncooked, the RDS content of PS-RPT-Q was higher than that of PS-Q-RPT, while the SDS content was the opposite. In the binary system, the RDS content of PS-Q was lower than that of PS-RPT, while the SDS content was the opposite, indicating that quercetin is more effective than rice peptide in prolonging starch digestion time.

[0132] Table 4 In vitro digestibility of uncooked food in different groups

[0133]

[0134]

[0135] Note: If the superscript letters of the data in the same column are different, it means there is a significant difference (P < 0.05); if the superscript letters are the same, it means there is no significant difference (P > 0.05).

[0136] Table 5 In vitro digestibility of different groups after cooking

[0137] Sample RDS (%) SDS (%) RS(%) <![CDATA[PS native ]]> <![CDATA[98.77±00.74 a ]]> <![CDATA[0.95±0.86 b ]]> <![CDATA[0.27±1.22 e ]]> <![CDATA[PS control ]]> <![CDATA[90.52±2.45 b ]]> <![CDATA[8.04±1.56 a ]]> <![CDATA[1.43±0.89 d ]]> PS-RPT <![CDATA[80.83±0.11 c ]]> <![CDATA[4.78±0.55 a ]]> <![CDATA[14.39±0.44 c ]]> PS-Q <![CDATA[70.27±2.55 d ]]> <![CDATA[4.94±1.66 a ]]> <![CDATA[24.79±0.89 b ]]> PS-RPT-Q <![CDATA[66.57±1.68 e ]]> <![CDATA[3.55±1.90 ab ]]> <![CDATA[29.88±3.57 e ]]> PS-Q-RPT <![CDATA[65.42±1.43 e ]]> <![CDATA[4.82±1.10 a ]]> <![CDATA[29.75±2.53 e ]]>

[0138] Note: If the superscript letters of the data in the same column are different, it means there is a significant difference (P < 0.05); if the superscript letters are the same, it means there is no significant difference (P > 0.05).

[0139] In summary, after heat-moisture treatment, the swelling of potato starch and its composites significantly decreased, with the composites exhibiting a greater reduction. Of the two ternary composites, the composite prepared according to the order of potato starch, rice peptide, and quercetin addition exhibited superior swelling inhibition. Heat-moisture treatment effectively reduced the gelatinization capacity of starch. Compared with native starch, the peak viscosity, hot paste viscosity, and cold paste viscosity of the heat-moisture-treated starch and its composites all decreased significantly, and the gelatinization time was prolonged. The gelatinization temperatures of the composites were lower than those of the PS control. In the ternary composites, the preferential mixing of starch and rice peptides effectively reduced starch viscosity. Heat-moisture treatment significantly increased the gelatinization temperature and prolonged the gelatinization time of starch, while the composites reduced the gelatinization temperature. In the ternary composites, the order of adding rice peptide and quercetin varied, resulting in different effects on the gelatinization temperature of starch. The preferential mixing of starch and quercetin was more effective in reducing the gelatinization temperature. Moisture-heat treatment conditions and the addition of quercetin can significantly change the crystal structure of starch granules. The starch-quercetin binary system is more effective in protecting the starch crystalline region during moist-heat treatment than the starch-rice peptide binary system. In the ternary composite system, the preferential mixing of starch and quercetin can better maintain the density and order of starch. The ternary composite system is better than the binary system in reducing the digestibility of starch. The different order of adding rice peptides and quercetin has different effects on the digestibility of the ternary system. Regardless of whether it is cooked or uncooked, the preferential mixing of starch and quercetin can better improve the digestibility of starch and prolong the digestion time.

[0140] It can be seen that heat-moisture treatment, the interaction between rice peptides and starch granules, the interaction between quercetin and starch granules, and the different addition orders of rice peptides and quercetin in the ternary system all affect the digestibility of potato starch.

[0141] Comparative Example 2

[0142] The difference from Example 2a is that catechins are not included. All other aspects are the same as Example 2a. Specifically, 20 g of potato starch (dry basis) was mixed with deionized water to a moisture content of 35% and equilibrated at room temperature for 24 hours. Then, 10% by weight of pea peptide (dry basis) of the potato starch was added and stirred. The mixture was placed in a reactor and reacted in a 100°C forced air oven for 1 hour. The reaction was continued in a 100°C forced air oven for 17 hours. The mixture was removed, cooled to room temperature, and placed in a 37°C forced air oven for 24 hours. The mixture was then pulverized and passed through a 100-mesh sieve. The resulting sample was designated PS-PPT (PPT stands for pea peptide, PS stands for potato starch).

[0143] The difference from Example 2 (b) is that pea peptide is not included. All other aspects are the same as Example 2 (b). Specifically, 20 g of potato starch (dry basis) was mixed with deionized water to a moisture content of 35% and equilibrated at room temperature for 24 hours. Then, catechins (10% by weight, based on the dry basis of the potato starch) were added and stirred. The mixture was placed in a reactor and reacted in a 100°C forced air oven for 1 hour. The reaction was continued in a 100°C forced air oven for 17 hours. The mixture was removed, cooled to room temperature, and placed in a 37°C forced air oven for 24 hours. The mixture was then pulverized and passed through a 100-mesh sieve. The resulting sample was designated PS-C (C represents catechins).

[0144] The sample obtained in Example 2a was recorded as PS-PPT-C, and the sample obtained in Example 2b was recorded as PS-C-PPT.

[0145] The potato starch without pea peptide and catechin and only subjected to wet heat treatment was used as the control group. Specifically, 20g of potato starch dry basis was mixed with deionized water to make the moisture content of the potato starch sample reach 35%, and then equilibrated at room temperature for 24 hours. Then, it was placed in a reactor and placed in a 100℃ forced air oven to react for 1 hour; then the reaction was continued in a 100℃ forced air oven for 17 hours; it was taken out and cooled to room temperature, placed in a 37℃ forced air oven for 24 hours, and then crushed and passed through a 100-mesh sieve. The obtained sample was recorded as PS control .

[0146] Potato starch without pea peptides and catechins added and without heat treatment is labeled as PS native .

[0147] The above PS control , PS-PPT, PS-C, PS-PPT-C, PS-C-PPT and PS native Perform the following tests:

[0148] (1) Determination of expansion degree: The specific method is the same as (1) of Comparative Example 1. The results are shown in Table 6. As can be seen from Table 6, the expansion degree of all samples increases with increasing temperature. native After heat treatment, the starch with pea peptides and catechins showed a lower swelling degree, which was different from the potato starch PS in the control group. control There are obvious differences. The expansion of the PS-C group is slightly greater than that of the PS-PPT group. The expansion of the PS-C-PPT group is slightly greater than that of the PS-PPT-C group.

[0149] Table 6 Expansion data of different groups

[0150] Sample 60℃ 70℃ 80℃ 90℃ <![CDATA[PS native ]]> <![CDATA[nd a ]]> <![CDATA[nd a ]]> <![CDATA[nd a ]]> <![CDATA[nd a ]]> <![CDATA[PS control ]]> <![CDATA[5.09±0.31 bc ]]> <![CDATA[5.46±0.16 d ]]> <![CDATA[7.98±0.06 b ]]> <![CDATA[8.85±0.21 b ]]> PS-C <![CDATA[5.52±0.82 b ]]> <![CDATA[6.11±0.73 b ]]> <![CDATA[7.68±0.50 b ]]> <![CDATA[8.42±0.20 b ]]> PS-PPT <![CDATA[4.21±0.79 c ]]> <![CDATA[4.71±0.32 cd ]]> <![CDATA[5.26±0.25 d ]]> <![CDATA[7.29±0.29 c ]]> PS-C-PPT <![CDATA[5.05±0.28 bc ]]> <![CDATA[5.98±0.39 b ]]> <![CDATA[6.79±0.40 c ]]> <![CDATA[8.32±0.99 b ]]> PS-PPT-C <![CDATA[4.81±0.53 bc ]]> <![CDATA[5.71±0.39 bc ]]> <![CDATA[6.65±0.17 c ]]> <![CDATA[7.78±0.37 bc ]]>

[0151] Note: Nd represents complete expansion, and the expansion degree was not measured. Different superscript letters in the same column of data indicate significant differences (P < 0.05); identical superscript letters indicate no significant differences (P > 0.05).

[0152] (2) Viscosity measurement: The specific method is the same as (2) in Comparative Example 1, and the viscosity and temperature curve is saved. The results are as follows: Figure 4 As shown in Table 7, the pasting time of the sample under the wet heat treatment condition is significantly longer than that of PS native , the paste temperature is also higher. Compared with PS native The peak viscosity, hot paste viscosity and cold paste viscosity of the samples treated with wet heat also showed a significant decrease, indicating that wet heat treatment can effectively reduce the gelatinization properties of starch. When performing wet heat treatment on starch, it is necessary to select appropriate treatment conditions and time to avoid over-treatment and damage to the structure of starch to ensure optimal gelatinization properties. Among the five samples treated with wet heat, the peak viscosity, hot paste viscosity and cold paste viscosity of the composite (binary and ternary) were lower than those of PS. control The reason for this is that the complex's structure is less conducive to water absorption and exhibits improved thermal stability. The ternary system, in which the two additives act together, is more effective in inhibiting starch lacustrine formation. Experiments have shown that the ternary system is superior to the binary system in reducing starch viscosity. As shown in Table 7, the peak viscosity, hot paste viscosity, and cold paste viscosity of PS-C-RPT are all lower than those of PS-C.

[0153] Table 7 Viscosity characteristics data of different groups

[0154] sample PT / ℃ PV / BU HV / BU CV / BU BD / BU SB / BU <![CDATA[PS native ]]> 66.8 4344 1404 2560 3188 628 <![CDATA[PS control ]]> 87.4 31 77 47 0 47 PS-C 83.2 37 55 19 0 19 PS-PPT 87.7 11 18 7 1 8 PS-PPT-C 81.1 17 26 9 0 9 PS-C-PPT 83.8 14 21 7 1 8

[0155] (3) Determination of thermodynamic properties (differential calorimetry analysis). The specific method is the same as (3) of Comparative Example 1. The results are shown in Table 8. Compared with the physically mixed samples, the gelatinization temperatures of potato starch and its composites increased after wet heat treatment, while the enthalpy values decreased. In addition, the interaction between starch and pea peptides, and starch and catechins will change the thermodynamic properties of the compounds, thereby further reducing the enthalpy change value. PS-C group and PS control Compared with the samples in the PS-PPT group, the gelatinization temperature and enthalpy change of PS-C were lower. control Compared with the samples in the group, the gelatinization temperature of PS-PPT is slightly higher, but the enthalpy change is slightly lower. native , T o 、T p and T c There has also been an increase.

[0156] Table 8 Thermodynamic properties data of different groups

[0157]

[0158]

[0159] Note: If the superscript letters of the data in the same column are different, it means there is a significant difference (P < 0.05); if the superscript letters are the same, it means there is no significant difference (P > 0.05).

[0160] (4) X-ray diffraction test: the specific method is the same as (4) in Comparative Example 1, and the results are as follows: Figure 5 As shown, PS native The samples of the group showed peaks at 6°, 14°, 17.5°, 20°, 22°, and 24°; control The peaks of the PS-PPT group were at 14.5°, 17.5°, and 23°; the peaks of the PS-C group were at 15°, 17°, and 23°; the peaks of the PS-PPT group were at 14.5°, 17.5°, and 23°; the peaks of the PS-C-PPT group were at 16.5° and 22.5°; and the peaks of the PS-PPT-C group were at 16° and 23°. native It is type B, PS after wet heat treatment control It becomes an A-type crystal structure, PS-PPT also has an A-type crystal structure, and PS-C, PS-PPT-C, and PS-C-PPT all have C+V-type crystal structures.

[0161] (5) Determination of in vitro digestibility: The specific method is the same as (5) of Comparative Example 1. The in vitro digestibility results of different groups under steaming and uncooking conditions are shown in Tables 9 and 10, respectively.

[0162] As can be seen from Table 9, under the conditions of wet heat treatment and gelatinization at 100℃, PS control Group and PS native Group comparison, PS control The RDS content in the potato starch decreased, while the SDS content increased. This indicates that heat treatment can significantly reduce the digestibility of potato starch and induce the conversion of RDS into SDS, thereby improving its slow digestibility. Analysis of Table 10 shows that under heat treatment conditions with a moisture content of 35%, PS control Group and PS nativeCompared with the PS-PPT group, the former showed reduced RDS and RS content. Compared with the PS-PPT group, the PS-C group showed lower RDS and SDS levels, while higher RS content. The difference in RDS content between the catechin-starch complex and the pea peptide-starch complex may be due to their different chemical structures. The higher RS content of the catechin-starch complex compared to the protein-starch complex may be due to the ability of catechins to form a more compact structure, making starch more difficult to break down during digestion. In addition, catechins can form cross-links with starch, further enhancing its stability and resistance to digestion. Therefore, compared with the pea peptide-starch complex, the polyphenol-starch complex has a higher RS content.

[0163] Table 10 shows that, compared to the data for the steamed samples (Table 9), the RDS content of the uncooked samples was lower than that of the steamed samples under the same processing conditions, while the SDS and RS contents were higher. This is because the steaming process involves heating and moisture treatment, which changes the structure and physical properties of starch molecules, leading to an increase in RDS content. Steaming breaks down the crystalline structure of starch granules, releasing starch chains encapsulated by water. These starch chains are more easily degraded by enzymes during digestion, and therefore no longer resist digestion. This, in turn, results in lower RS content in the steamed samples compared to the ungelatinized samples.

[0164] Table 9 In vitro digestibility data of different groups of cooking

[0165] Sample RDS (%) SDS (%) RS(%) <![CDATA[PS native ]]> <![CDATA[98.28±1.85 a ]]> <![CDATA[1.31±2.83 b ]]> <![CDATA[0.42±0.98 d ]]> <![CDATA[PS control ]]> <![CDATA[91.76±2.24 b ]]> 6.41±3.03 1.82±0.78 PS-C <![CDATA[69.2692±2.00 d ]]> <![CDATA[5.29±5.02 ab ]]> <![CDATA[25.44±3.01 b ]]> PS-PPT <![CDATA[81.01±2.94 c ]]> <![CDATA[8.09±5.02 a ]]> <![CDATA[10.89±2.18 c ]]> PS-C-PPT <![CDATA[64.72±0.77 e ]]> <![CDATA[4.29±1.87 ab ]]> <![CDATA[30.98±1.10 a ]]> PS-PPT-C <![CDATA[64.70±0.89 e ]]> <![CDATA[4.55±0.22 ab ]]> <![CDATA[30.75±1.11 a ]]>

[0166] Note: If the superscript letters of the data in the same column are different, it means there is a significant difference (P < 0.05); if the superscript letters are the same, it means there is no significant difference (P > 0.05).

[0167] Table 10 In vitro digestibility data of different groups without cooking

[0168] Sample RDS (%) SDS (%) RS(%) <![CDATA[PS native ]]> <![CDATA[31.78±2.42 f ]]> <![CDATA[26.14±1.69 b ]]> <![CDATA[42.09±0.72 b ]]> <![CDATA[PS control ]]> <![CDATA[59.88±0.22 a ]]> <![CDATA[30.33±4.77 a ]]> <![CDATA[9.79±4.54 e ]]> PS-C <![CDATA[46.02±1.10 c ]]> <![CDATA[22.54±1.76 bc ]]> <![CDATA[31.43±2.86 c ]]> PS-PPT <![CDATA[65.93±6.07 b ]]> <![CDATA[14.99±4.58 e ]]> <![CDATA[19.08±1.49 d ]]> PS-C-PPT <![CDATA[34.44±0.43 e ]]> <![CDATA[14.33±0.86 e ]]> <![CDATA[51.23±1.29 a ]]> PS-PPT-C <![CDATA[40.03±0.11 d ]]> <![CDATA[18.82±1.31 cd ]]> <![CDATA[41.14±1.20 b ]]>

[0169] Note: If the superscript letters of the data in the same column are different, it means there is a significant difference (P < 0.05); if the superscript letters are the same, it means there is no significant difference (P > 0.05).

[0170] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for improving the physicochemical properties of starch, characterized in that: The method includes a or b: a. Mix starch and protein peptide, react at 100℃ for 1h, then mix with phenolic substances and react at 100℃ for 17h; b. Mix starch with phenolic substances, react at 100°C for 1 hour, then mix with protein peptides, and react at 100°C for 17 hours; The starch includes potato starch; the protein peptide includes rice peptide or pea peptide; and the phenolic substance includes quercetin or catechin.

2. The method according to claim 1, characterized in that The physical and chemical properties of starch include swelling capacity, gelatinization temperature, viscosity, crystal structure, density and order.

3. The method according to claim 2, characterized in that If you want to reduce the swelling or viscosity of starch, choose a; if you want to lower the gelatinization temperature of starch or maintain the density and order of starch, choose b.

4. The method according to claim 1, wherein The weight of the protein peptide is 10% of the dry weight of starch; the weight of the phenolic substance is 10% of the dry weight of starch.

5. A method for improving the digestibility of starch, characterized in that: The method comprises the following steps: mixing starch with water until the moisture content of the starch reaches 35%, mixing with phenolic substances after equilibration at room temperature, reacting at 100°C for 1 hour, adding protein peptides, and reacting at 100°C for 17 hours; the starch comprises potato starch; the protein peptides comprise rice peptides or pea peptides; and the phenolic substances comprise quercetin or catechins.

6. The method according to claim 5, characterized in that The room temperature equilibration time is 24 hours.

7. The method according to claim 5, characterized in that The weight of the protein peptide is 10% of the dry weight of starch; the weight of the phenolic substance is 10% of the dry weight of starch.

8. A low digestibility potato starch compound powder, characterized in that: The invention relates to a method for preparing a novel nanostructured carbon foam comprising mixing potato starch, protein peptide and phenolic substances in the order of potato starch, phenolic substances and protein peptide, and performing wet heat treatment to obtain the nanostructured carbon foam; the weight of the protein peptide is 10% of the weight of the starch on a dry basis; the weight of the phenolic substances is 10% of the weight of the starch on a dry basis; the protein peptide comprises rice peptide or pea peptide; and the phenolic substances comprises quercetin or catechin.

9. The method for preparing the low digestibility potato starch compound powder according to claim 8, characterized in that: The method comprises the following steps: mixing potato starch with water until the moisture content of the potato starch reaches 35%, mixing with phenolic substances after equilibration at room temperature, reacting at 100° C. for 1 hour, adding protein peptides, and reacting at 100° C. for 17 hours; the protein peptides comprise rice peptides or pea peptides; and the phenolic substances comprise quercetin or catechins.

10. Use of the method according to any one of claims 5 to 7, the low digestibility potato starch compound powder according to claim 8, or the preparation method according to claim 9 in the preparation of low GI food.